Importance of Mass Transport in High Energy Density Lithium‐Sulfur Batteries Under Lean Electrolyte Conditions. Issue 5 (1st March 2022) - Li, Shanglin; Ishikawa, Shota; Liu, Jiali; Ueno, Kazuhide; Dokko, Kaoru; Inoue, Gen; Watanabe, Masayoshi
Abstract: The operation of a lithium‐sulfur (Li−S) battery under lean electrolyte conditions is essential for enhancing the energy density to a practical level. It is rather challenging to reduce the amount of electrolyte in Li−S cells because the discharge reactions of sulfur (Li2 S x formation: x =8−1) occur via a fully dissolution/precipitation conversion mechanism in conventional electrolyte solutions. Therefore, the use of sparingly solvating electrolytes has been reported as an effective method to reduce the electrolyte content in Li−S cells. However, the majority of related research to date has been based on the use of an excess amount of electrolyte and low S loading. In this study, we investigated the performance of Li−S cells using cathodes with a relatively high S loading (>4 mg cm −2 ) under lean electrolyte conditions of sparingly solvating electrolytes. The products of inhomogeneous discharge reactions occurring at the separator side in the Li−S cell cathodes blocked the void spaces of the cathode, and the porosity of the cathode decreased due to the expansion of the active material. In addition, the ion pathway toward the interior parts of the electrode (close to the current collector) was hindered, and further discharge reactions were inhibited. The inhomogeneous discharge reactions could be alleviated by enhancing the transport properties of the electrolyte and adequately maintaining the porous structure of the cathode by incorporating an additive in it. The effects of these changes on the Li−S cell performance were also further confirmed by numerical simulations. Abstract : For Lithium‐sulfur batteries under lean electrolyte conditions : To realise high energy density Li−S batteries with sparingly solvating electrolytes, Li−S cells were fabricated using highly sulfur‐loaded cathodes under lean electrolyte conditions. The inhomogeneous discharge reactions at the separator side in the cathodes, which negatively affected the cell performance, could be alleviated by enhancing the transport properties of the electrolyte and adequately maintaining the porous cathode structure.